The Role of SDF-1/CXCR4/CXCR7 in Neuronal Regeneration after Cerebral Ischemia - Cheng, Xi; Wang, Huibin; Zhang, Xiuchun; Zhao, Shanshan; Zhou, Zhike; Mu, Xiaopeng; Zhao, Chuansheng; Teng, Weiyu (Frontiers in Neuroscience, 2017)
Abstract: Stromal cell-derived factor-1is a chemoattractant produced by bone marrow stromal cell lines. It is recognized as a critical factor in the immune and central nervous systems as well as exerting a role in cancer. SDF-1 activates two G protein-coupled receptors, CXCR4 and CXCR7; these are expressed in both the developing and mature central nervous systems and participate in multiple physiological and pathological events, e.g. inflammatory response, neurogenesis, angiogenesis, hematopoiesis, cancer metastasis, and HIV infection. After an ischemic stroke, SDF-1 levels robustly increase in the penumbra regions and participate in adult neural functional repair. Here we will review recent findings related to SDF-1 and its receptor, analyze their functions in neurogenesis after brain ischemic injury: i.e. how the system promotes the proliferation, differentiation and migration of neural precursor cells and mediates axonal elongation and branching.